In vitro transformation of Capsicum frutescens for the production of vanillin - Chee, Jenn Yang (2017)
The need for an alternative approach to the production of vanillin that is generally regarded as safe and “natural” is receiving much attention in the current market trend. This is due to the high market price of natural vanilla extract compared to cheap synthetic vanillin (a major flavouring compound in vanilla extract). Hence, this research was aimed at producing vanillin by the in vitro transformation of Capsicum frutescens (chilli plant), an alternative to the current production systems using a plant-based approach. Plant tissues which are transformed with genes of feruloyl-CoA synthetase (fcs) and enoyl-CoA hydratase (ech) from bacterium Amycolatopsis sp. ATCC 39116 or the gene of vanillin synthase (VpVAN) from Vanilla planifolia were expected to biosynthesize vanillin using ferulic acid as the precursor. An optimisation study of plant tissue culture conditions for the chilli plant was first conducted to regenerate chilli explants into callus for the prospective production of target phenolics, particularly vanillin. Sterile cultures were established from the seeds of C. frutescens after a surface sterilisation with 70% (v/v) ethanol for 5 min, followed by 15–20% (v/v) commercial bleach for 20 min. MS media supplemented with 0.5 mg/l kinetin and 2.0 mg/l 2,4-D induced callusing from cotyledon, hypocotyl and root explants, with the highest amount of biomass being produced from the hypocotyl explants. High performance liquid chromatography (HPLC) analyses of cultured plant tissues of C. frutescens revealed only trace amounts of vanillin and ferulic acid in the analysed tissues. Ferulic acid (the precursor) feeding of callus cultures for one-month period revealed no significant elicitation of vanillin production. Subsequently, the fcs, ech and VpVAN genes have been codon optimised and cloned separately into transformation vectors via Gateway Cloning, Golden Gate Cloning or double restriction-ligation cloning, with the cauliflower mosaic virus 35S promoter or nopaline synthase promoter upstream of the genes. The constructed expression vectors were delivered into hypocotyl explants of C. frutescens through microprojectile bombardment using the optimised parameters of 1.6 µm gold particle size, 1350 psi He pressure and 6 cm target distance. Calli that were transformed with both fcs and ech genes or the VpVAN gene showed significant gene expression levels of the transgenes (up to 131.3-fold, 0.4-fold and 8.4-fold high for fcs, ech and VpVAN, respectively) compared to no detectable expression levels in untransformed calli and remarkable increases in vanillin (up to 1231.7 μg per gram tissue), vanillin-β-D-glucoside (up to 340.5 μg per gram tissue) and vanillic acid (up to 604.6 μg per gram tissue) contents. These findings lave laid a foundation for future improvements in the use of genetic manipulation approaches in chilli plants as an alternative to the production of vanillin.